Investigating the impact of challenge and hindrance techno stressors on academic performance in online learning environments - Muhammad Z. I. Lallmahomed (Discover Education)
Abstract In the post Covid-19 era, technology is now an integral part of the curriculum where in-classroom learning has been replaced by fully online and blended teaching. The rapid change to novel online learning environment, have left students exposed to the risks of techno stress. Given the dearth of studies on students, this research seeks to investigate the impact of challenge/hindrance techno stressors on students’ satisfaction, burnout and engagement. Ultimately, the impact of these intervening variables on academic performance is examined. 198 students were surveyed, and results demonstrate that hindrance stressors are negatively related to satisfaction and engagement while contributing positively to burnout. Challenge stressors are positively related student’s satisfaction and engagement. The findings also show that satisfaction partially mediate the relationship between both hindrance/challenge stressors and academic performance. Gender has been found to be moderating the relationship between hindrance stressors and burnout. Implications for higher education institutions are discussed.